Both gain‐of‐function and loss‐of‐function de novo CACNA1A mutations cause severe developmental epileptic encephalopathies in the spectrum of Lennox‐Gastaut syndrome. (29th August 2019) - Jiang, Xiao; Raju, Praveen K.; D'Avanzo, Nazzareno; Lachance, Mathieu; Pepin, Julie; Dubeau, François; Mitchell, Wendy G.; Bello‐Espinosa, Luis E.; Pierson, Tyler M.; Minassian, Berge A.; Lacaille, Jean‐Claude; Rossignol, Elsa
Abstract: Objective: Developmental epileptic encephalopathies (DEEs) are genetically heterogeneous severe childhood‐onset epilepsies with developmental delay or cognitive deficits. In this study, we explored the pathogenic mechanisms of DEE‐associated de novo mutations in the CACNA1A gene. Methods: We studied the functional impact of four de novo DEE‐associated CACNA1A mutations, including the previously described p.A713T variant and three novel variants (p.V1396M, p.G230V, and p.I1357S). Mutant cDNAs were expressed in HEK293 cells, and whole‐cell voltage‐clamp recordings were conducted to test the impacts on CaV 2.1 channel function. Channel localization and structure were assessed with immunofluorescence microscopy and three‐dimensional (3D) modeling. Results: We find that the G230V and I1357S mutations result in loss‐of‐function effects with reduced whole‐cell current densities and decreased channel expression at the cell membrane. By contrast, the A713T and V1396M variants resulted in gain‐of‐function effects with increased whole‐cell currents and facilitated current activation (hyperpolarized shift). The A713T variant also resulted in slower current decay. 3D modeling predicts conformational changes favoring channel opening for A713T and V1396M. Significance: Our findings suggest that both gain‐of‐function and loss‐of‐function CACNA1A mutations are associated with similarly severe DEEs and that functional validation is required to clarify the underlying molecular mechanisms and to guide therapies.